دور عقد تحويل الفاتورة في تمويل المؤسسات الصغيرة المتوسطة في الجزائر - طلحي, سماح; عوادي, عبد القادر; عوام, نسرين (جامعة الوادي - University of Eloued, 2021)
تعد المؤسسات الصغيرة والمتوسطة المحرك الأساسي للتنمية الاقتصادية لذا يتعين الإحاطة بجميع المشاكل التي تواجهها والتي من أهمها مشكلة التمويل. فرغم تعدد مصادر التمويل المتاحة أمامها يبقى من الضروري الاهتمام بالتقنيات التمويلية الحديثة والتي من بينها عقد تحويل الفاتورة الذي أثبت نجاعته في تمويل المؤسسات الصغيرة والمتوسطة في البلدان المتقدمة. أما عن واقع تطبيق الفاكتورينغ في تمويل المؤسسات الصغيرة والمتوسطة الجزائرية فإنه رغم توفر الأرضية القانونية والتنظيمية له، يظل لجوء المؤسسات الصغيرة والمتوسطة لهذه التقنية التمويلية جد محدود نظرا لحداثة تطبيقها في الجزائر من جهة وعدم إدراك المفاهيم الأساسية المتعلقة بها وأهميتها كبديل تمويلي فعال من جهة أخرى. The small and medium enterprises play a key role in economic development, so it is highly important to understand the problems that face them, notably that of financing. For despite the availability of many financing sources, it is imperative to consider modern financing techniques such is Factoring which has proved its efficiency in financing small and medium enterprises in advanced countries. Despite there being a juridical and organisational context for Factoring as an alternative in the financing of algerian small and medium enterprises, the latter’s recourse to it remains limited because of the newness of its implementation in Algeria on the one hand, and the incomprehension of the basic concepts covering modern financing and its importance as an efficient financing alternative on the other hand
The Role of the Factoring in financing Small and Medium Enterprises in Algeria
مقال
Keywords: عقد تحويل الفاتورة ; فاكتورينغ ; تمويل المؤسسات الصغيرة والمتوسطة ; تمويلات حديثة